2002
DOI: 10.1161/01.cir.0000029093.93362.fc
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensinogen Gene Promoter Region Variant Modifies Body Size–Ambulatory Blood Pressure Relations in Hypertension

Abstract: Background-The extent to which genes modify the relationship between risk factors for hypertension and blood pressure (BP) is unclear. As angiotensinogen is expressed in adipose tissue and angiotensinogen (AGT) gene promoter variants influence the production of angiotensinogen, we evaluated the role of AGT gene variants as potential modifiers of body size-BP relations. Methods and Results-Five hundred twenty-one hypertensives of African origin sampled from a group with a high mean body mass index (BMI) had 24-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 22 publications
0
35
0
1
Order By: Relevance
“…In contrast, previous work has shown adiposity-family history interactions with regard to diabetes 38 and breast cancer, 39 and another has shown smoking-FHCHD interactions on cardiovascular disease mortality 40 in adults. Currently, there is considerable interest in gene-adiposity interactions on BP [17][18][19] using DNA technologies. These reports have shown that the -20A-C polymorphism in the AGT promotor region, 18 ACE I/D, 19 and Arg16Gly polymorphism of the beta 2 adrenoreceptor 2 interact with various indices of adiposity (BMI and waist-to-hip ratio) and various BP phenotypes (resting and ambulatory BP).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, previous work has shown adiposity-family history interactions with regard to diabetes 38 and breast cancer, 39 and another has shown smoking-FHCHD interactions on cardiovascular disease mortality 40 in adults. Currently, there is considerable interest in gene-adiposity interactions on BP [17][18][19] using DNA technologies. These reports have shown that the -20A-C polymorphism in the AGT promotor region, 18 ACE I/D, 19 and Arg16Gly polymorphism of the beta 2 adrenoreceptor 2 interact with various indices of adiposity (BMI and waist-to-hip ratio) and various BP phenotypes (resting and ambulatory BP).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is considerable interest in gene-adiposity interactions on BP [17][18][19] using DNA technologies. These reports have shown that the -20A-C polymorphism in the AGT promotor region, 18 ACE I/D, 19 and Arg16Gly polymorphism of the beta 2 adrenoreceptor 2 interact with various indices of adiposity (BMI and waist-to-hip ratio) and various BP phenotypes (resting and ambulatory BP). In the context of human growth and BP, Lever and Harrap 41 have suggested that a master gene, which they refer to as 'basal growth potential gene', has pleiotropic control over somatic growth, obesity and BP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many additional polymorphisms, however, have been identified in the AGT gene, including an additional promoter polymorphism at −20. This polymorphism is also interesting, since depending on the genotype different response elements are generated, including those for estrogen receptor α, upstream regulatory factor and members of the COUP-TF family, which correlates with different phenotypes, including pregnancydependent variations in AGT levels, non-modulating hypertension and an altered relationship between BMI and blood pressure (Zhao et al 1999;Morgan et al 2000;Hilgers et al 2001;Tiago et al 2002). Current research efforts address the haplotype structure of the AGT gene, which should be comparatively easy given the short length of the gene of only ∼12 kb.…”
Section: Polymorphisms In the Angiotensinogen Genementioning
confidence: 99%
“…Інсерційно-делеційний полімор-фізм 16-го інтрону гена ангіотензинперет-ворювального ферменту (AСЕ) визначали із застосуванням полімеразної ланцюгової реакції (ПЛР) із наступним електрофорезом отриманих ампліфікатів [12]. Для виявлення поліморфізмів наступних генів: G 894 →T -поліморфізм 7-го екзону гена ендотеліальної NO-синтази (eNOS) [13], Arg 60 →His -полі-морфізм гена, що кодує одну з індуцибель-них субодиниць протеасоми (LMP2) [14], Met 235 →Thr -поліморфізм гена ангіотензи-ногена (AGT) [15], A 1166 →C -поліморфізм гена рецептора 1-го типу ангіотензину ІІ (ATR1) [16], C -1562 →T -поліморфізм гена металопротеїнази 9 (MMP9) [17], Т -381 →C -поліморфізм гена натрійуретичного пепти-ду типу В (NPPB) [18] застосовували ПЛР із наступним аналізом довжини рестрикційних фрагментів. C -1306 →T -поліморфізм гена металопротеїнази 2 (MMP2) визначали із застосуванням алель -специфічної ПЛР [19].…”
Section: методикаunclassified